Strategy Formulation for a Traditional Sundanese Restaurant: SWOT, IFE-EFE-IE, and QSPM Analysis of Sari Rasa Sambel Hejo Pusat - Harsya Jayaditya; Sunu Puguh Hayu Triono (Fundamental and Applied Management Journal, 2026)
The increasing competitiveness of Indonesia's culinary industry requires traditional restaurants to formulate adaptive business strategies to sustain competitiveness and long-term growth. Sari Rasa Sambel Hejo Pusat (SRSH), a traditional Sundanese restaurant operating since 1968 in Purwakarta, faces challenges related to market competition, service quality, and limited utilization of digital marketing. This study aims to analyze the internal and external business environment of SRSH and formulate priority business development strategies to support its future growth and sustainability. This study employed a descriptive qualitative case-study approach. Data were collected during the 2025–2026 research period through in-depth interviews, observations, and documentation. Six key informants participated in the study, consisting of three internal stakeholders (owner, branch manager, and partnership manager) and three external stakeholders (competitor, supplier, and government representative). Data were analyzed using the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal–External (IE) Matrix, SWOT Analysis, and Quantitative Strategic Planning Matrix (QSPM).  The IFE analysis produced a score of 3.09, indicating a strong internal position characterized by product authenticity, customer loyalty, and extensive business experience. The EFE analysis generated a score of 2.98, demonstrating the company’s ability to capitalize on external opportunities while managing environmental threats. These results positioned SRSH in Cell IV (Grow and Build) of the IE Matrix. SWOT analysis generated four strategic alternatives, while the QSPM identified optimizing digital marketing and online platform utilization as the highest-priority strategy, achieving a Total Attractiveness Score (TAS) of 6.24. SRSH possesses strong growth potential supported by favorable internal capabilities and external opportunities. Strengthening digital marketing represents the most attractive strategic option to enhance competitiveness, expand market reach, and support long-term business sustainability.